Legitimating Contexts, Immigrant Power, and Exclusionary Actions. (7th February 2015) - Ebert, Kim; Okamoto, Dina
Abstract: In multi-ethnic nation-states, opposition to immigration has manifested itself in attitudes and behaviors. Past research has typically focused on anti-immigrant attitudes, and relied on threat and competition theories to explain patterns in such attitudes. These theories suggest that perceived threats stemming from new influxes or large concentrations of immigrants should prompt dominant groups to protect their interests, leading to anti-immigrant attitudes. We extend the literature with a focus on anti-immigrant activity, and introduce the legitimating contexts model, which argues that dominant groups may actually hesitate to engage in exclusionary public actions in places where the political and demographic strength of immigrant and ethnic groups is strong. In contrast to theories of group threat, we contend that in contexts with low levels of immigrant political power and demographic strength, anti-immigrant activity is less likely to be noticed, let alone challenged, and thus more likely to become part of the status quo. Extending political opportunity theory, we also claim that conservative elites and voters in local areas coupled with low levels of threat further legitimate anti-immigrant activity. We test these ideas using a new data set of exclusionary action targeted at immigrants in over 50 U.S. metropolitan areas. In support of the legitimating contexts model, we find that low levels of demographic and political threat—when immigrants enjoy less power—alone and coupled with a higher share of conservative voters act to legitimate and encourage restrictive events on the part of noninstitutional actors. En naciones multiétnicas la oposición a la inmigración se ha manifestado en actitudes y conductas. La mayoria de investigaciones previas se han concentrado en teorías de amenaza y de competencia para explicar estas actitudes anti-inmigrantes. De acuerdo con estas teorías, la percepción de amenaza que surge de la llegada o incremento en la concentración de población inmigrante lleva a los grupos dominantes a proteger sus intereses y a desarrollar actitudes anti-inmigrantes. En este artículo analizamos las actitudes anti-inmigrantes a través del modelo del contexto legitimador que sostiene que los grupos dominantes vacilan en ejercer acciones públicas excluyentes en lugares donde los inmigrantes y grupos étnicos tienen poder político y demográfico. A diferencia de las teorías de amenaza colectiva, nosotros argumentamos que en contextos donde los inmigrantes tienen poco poder político y demográfico, es menos probable que las actitudes anti-inmigrantes sean visibles y también desafiadas, manteniendose así el status quo. Basados en la teoría de la oportunidad política, también argumentamos que en áreas con bajo nivel de amenaza, las élites y los votantes conservadores legitiman las actitudes anti-inmigrantes. Examinamos estas ideas sobre la base de un nuevo conjunto de datos sobre acciones excluyentes dirigidas a la población inmigrante en más de 50 áreas metropolitanas en los Estados Unidos. En concordancia con el modelo del contexto legitimador, encontramos que cuando existen bajos niveles de amenaza demográfica y política -es decir cuando los inmigrantes tienen menos poder- y cuando a la par existe una masa importante de votantes conservadores, estos factores, solos o de manera conjunta, legitiman y fomentan eventos restrictivos por parte de actores no-institucionales.